Draft genome sequence and gene annotation of Stemphylium lycopersici strain CIDEFI-216 - Franco, Mario Emilio Ernesto (2015)
Stemphylium lycopersici is a plant-pathogenic fungus that is widely distributed throughout the world. In tomatoes, it is one of the etiological agents of gray leaf spot disease. Here, we report the first draft genome sequence of S. lycopersici, including its gene structure and functional annotation.